Pendidikan Pancasila Inklusif di SD: Menyemai Toleransi dan Keberagaman melalui Kurikulum Merdeka - Saqjuddin Saqjuddin (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Pancasila education plays a strategic role in shaping the character of Indonesia’s younger generation, particularly in fostering values of tolerance and diversity. Within the context of the Merdeka Curriculum, which offers broader opportunities for character development, inclusive Pancasila education emerges as a relevant and transformative approach, especially at the elementary school level. This study aims to describe the implementation of inclusive Pancasila education in elementary schools and evaluate its impact on students’ attitudes toward diversity. Employing a descriptive qualitative approach, data were collected through observations, interviews, and document analysis in several elementary schools implementing the Merdeka Curriculum. The findings reveal that the integration of Pancasila values such as mutual cooperation (gotong royong), social justice, and humanity is reflected in contextual and participatory learning practices. Schools that adopt an inclusive approach have successfully created a learning environment that encourages respect for differences, including those related to religion, culture, and socioeconomic background. The study concludes that inclusive Pancasila education not only strengthens students’ national identity but also lays the foundation for building a pluralistic and democratic society from an early age. The study recommends enhancing teacher training, developing localized learning materials, and conducting continuous evaluation to ensure the sustainability of inclusive Pancasila education.